Effects of new and recycle electrodes on the mechanical properties of shielded metal arc welding (SMAW) / N Rajeswara Rao Apparow - N Rajeswara Rao, Apparow (2021)
Shielded Metal Arc Welding (SMAW) is a manual simple and common welding process using electrodes as filler material. There was a requirement welding electrode are recommended to be used once after opened from Vacuum pack followed by baking. It not recommended to rebake few times after removed from oven. This project is a study on the effect of welding from newly baked electrode, electrode after 1st rebake, 2nd rebake and 3rd rebake on the mechanical properties. The mechanical properties of the welding in this study are tensile test, impact test, bend test and hardness test. Based on the research all the mechanical properties was in acceptable range for all the multiple rebaked electrodes. There were no visible cracks found for all the bend test specimens. There was a slight trend of tensile properties reduction as the electrodes was more frequently baked. But the impact properties increase as the electrodes were more frequently baked. Hardness value is inconsistent but as average the hardness value increase as the electrodes were baked more times. The changes in the mechanical properties are estimated below 3% and can be consider almost insignificant. Hence there is an insignificant changes in the mechanical properties due to the multiple rebaking of electrodes.